2012
DOI: 10.1145/2185376.2185387
|View full text |Cite
|
Sign up to set email alerts
|

Authority server selection in DNS caching resolvers

Abstract: Operators of high-profile DNS zones utilize multiple authority servers for performance and robustness. We conducted a series of trace-driven measurements to understand how current caching resolver implementations distribute queries among a set of authority servers. Our results reveal areas for improvement in the ``apparently sound'' server selection schemes used by some popular implementations. In some cases, the selection schemes lead to sub-optimal behavior of caching resolvers, e.g. sending a significant am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 15 publications
5
31
0
Order By: Relevance
“…The median number of name servers configured per DNS zone on that name server, however, is 4.0, which means that not all queries from Google for domains hosted on that name server will be sent to that particular name server. Typical resolver implementations will distribute queries over all authoritative name servers for a domain, usually favoring servers with shorter RTTs [14].…”
Section: Distribution Of Queries Over Authoritative Name Serversmentioning
confidence: 99%
“…The median number of name servers configured per DNS zone on that name server, however, is 4.0, which means that not all queries from Google for domains hosted on that name server will be sent to that particular name server. Typical resolver implementations will distribute queries over all authoritative name servers for a domain, usually favoring servers with shorter RTTs [14].…”
Section: Distribution Of Queries Over Authoritative Name Serversmentioning
confidence: 99%
“…Since, the domain name resolution procedure can be considered as a node traversal problem, an optimal choice of the appropriate nodes can significantly improve the performance. Thus, the impact of the DNS server selection algorithms of popular DNS proxy server implementations is provided by the work [11].…”
Section: Related Workmentioning
confidence: 99%
“…Yu et al [14] found that various versions of DNS resolvers (notably BIND and PowerDNS) adjust the rate at which they query different root servers based on RTTs, sometimes in nonintuitive ways. BIND 9.7, for instance, preferentially queries root servers with greater RTTs.…”
Section: Likely Cause: Non-uniform Server Selection Algorithmsmentioning
confidence: 99%
“…PowerDNS, which is popular in Europe, on the other hand, exhibits a "spike distribution," causing it to almost exclusively contact the single lowest-RTT server [14]. Figure 6 shows the geographic distribution of servers whose query volumes increased by at least 100×; 62% of these servers are located in Europe, 20% in North America, 10% in Asia, 7% in Oceania, and the rest in South America and Africa.…”
Section: Likely Cause: Non-uniform Server Selection Algorithmsmentioning
confidence: 99%